Express Polymer Letters is renewing - Tamás Bárány; László Mészáros (eXPRESS Polymer Letters)
Express Polymer Letters has been published by the Department of Polymer Engineering at the Budapest University of Technology and Economics (BME) for 15 years. Under the guidance and dedicated work of Prof. József Karger-Kocsis and Prof. Tibor Czigány, it quickly developed into a prestigious journal and still holds its position as one of the leading journals in its field (JCR IF(2020) 4.161; Q1 in 'Polymer Science'). Since then, the world has changed a lot, both in science and computing, and Prof. Karger-Kocsis is no longer with us. In the last 15 years, the focus of polymer science research has also changed dramatically: e.g. the rise of graphene, functional and smart polymers, biopolymers like polylactic acid, and recycling and environmental issues. Readers' needs have also changed. A significant proportion of articles are being read on smartphones and tablets rather than at a computer desk or in a library.